A Review on Soil-Foundation-Interaction Models - Gaurav Pandey; Dhirendra Patel; Vishal Mourya; Rajesh Kumar; Suresh Kumar (Journal of Rehabilitation in Civil Engineering)
The process in which response of soil influences the motion of foundation and vice-versa, is known as Soil-Foundation Interaction (SFI). This paper deals with the different types of soil-foundation interaction models useful for structural as well as geotechnical engineers and researchers for safe and economical raft design. The study offers a gist of all the models in literature and their applications. Several approaches for analysis which include analytical methods and numerical methods have been described here. Analytical models based on Winklerian and Continuum approach have been discussed. Moreover, modified forms of such approaches have also been discussed. In general, all the models make use of a parameter known as Modulus of Subgrade Reaction to model soil interaction. This parameter can be calculated either through experiments or empirical formulas. Different numerical methods have also been presented along with a few literatures. Further, some of the studies on raft foundation are also included.